1994
DOI: 10.1002/j.1556-6676.1994.tb01734.x
|View full text |Cite
|
Sign up to set email alerts
|

Marital Status and Sex: Impact on Career Self‐Efficacy

Abstract: Bandura's (1977Bandura's ( , 1986 A n increasing number of empirical studies are investigating the career development process in general and variables related to the career behavior of women specifically. Hackett and Betz (1981) proposed a "self-efficacy" approach to the career development process of women. Self-efficacy theory is an element of Bandura's (1977) social cognitive learning theory, and self-efficacy expectations are one's beliefs in one's ability to perform a given behavior successfully. Partly on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2001
2001
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
(30 reference statements)
1
3
0
Order By: Relevance
“…The significant paths exclusive to females (selfefficacy to outcome expectations, and a strong relationship particularly between career self-efficacy in the Data/Things area and interests and career choices in both the Data/Things and People/Ideas areas) demonstrate the strong impact of self-efficacy. This finding confirms the literature on gender difference in career self-efficacy and its relationship to femaleor male-dominated occupations (Bonett, 1994;Kelly, 1993;Mathieu, Sowa, & Niles, 1993;Matsui, 1994;Wiljanen, 1996). Additionally, the findings from this study suggest that learning experiences have a greater influence on the development of career self-efficacy for female students than for male students.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The significant paths exclusive to females (selfefficacy to outcome expectations, and a strong relationship particularly between career self-efficacy in the Data/Things area and interests and career choices in both the Data/Things and People/Ideas areas) demonstrate the strong impact of self-efficacy. This finding confirms the literature on gender difference in career self-efficacy and its relationship to femaleor male-dominated occupations (Bonett, 1994;Kelly, 1993;Mathieu, Sowa, & Niles, 1993;Matsui, 1994;Wiljanen, 1996). Additionally, the findings from this study suggest that learning experiences have a greater influence on the development of career self-efficacy for female students than for male students.…”
Section: Discussionsupporting
confidence: 90%
“…Thus, career self-efficacy is a significant factor for female students' career aspirations, particularly for non-female traditional occupations (Mau, 2003;Post-Kammer & Smith, 1985;Rainey & Borders, 1997). Bonett (1994) found that females had lower self-efficacy than males for male-dominated occupations, while males had lower self-efficacy for traditionally female occupations. Similarly, high school male students demonstrated higher self-efficacy for male-dominated professions than their female counterparts (Wiljanen, 1996).…”
Section: Gender Differences In Career Developmentmentioning
confidence: 97%
“…Results of the study also indicate that a career and life planning course may produce a greater effect for women regarding their career decision-making self-efficacy than it does for men. This finding is not surprising, considering that other researchers have found that women tend to have lower levels of career self-efficacy than do men, especially in relation to nontraditional occupations (Betz & Hackett, 1981;Bonett, 1994;Stickel & Bonett, 1991). Betz ( 1992) discussed various barriers to women's career development that can lead to a narrowing of career choices to traditionally female professions and occupations.…”
Section: Discussionmentioning
confidence: 65%
“…Betz ( 1992) discussed various barriers to women's career development that can lead to a narrowing of career choices to traditionally female professions and occupations. It makes sense that a career and life planning course, which is designed to increase students' decision-making skills and challenge self-defeating ideas about career planning, will increase women's awareness of career possibilities more than it does men's because men feel less limited in their options in general (Bonett, 1994).…”
Section: Discussionmentioning
confidence: 99%